PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE PICTURE AND PICTURE TERHADAP TINGKAT PERHATIAN SISWA SD NEGERI MERUYUNG - Dewi Maulida; Venni Herli Sundi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The influence of the Picture and Picture type cooperative learning model on the level of attention of students at SDN Meruyung Depok. This study is based on a research hypothesis that suspects the influence of the Picture and Picture type cooperative learning model on the level of attention of class II students. The purpose of this study is to determine whether there is an influence of the Picture and Picture type cooperative learning model on the level of attention of students. The population used in this study was class II with a sample of 34 students. The instrument given was a questionnaire for the level of attention of students. This study was conducted using a quantitative experimental method. The success of this study was proven by the Paired Sample T test with the results showing a t-count value of 8.704> 2.035 and a sig. value of 0.000 <0.005, thus it can be concluded that there is an influence of the Picture and Picture type cooperative learning model on the level of attention of students.